Strings of pride the conservation and transmission of Dauin's rondalla tradition - Mascuñana, Rolando V. (Musika Jornal, 2012)
This paper primarily intends to document how the skills of playing and instrument making of rondalla were taught and learned in Dauin, and subsequently transmitted to your family members and those in the community. The participation of rondalla groups in public events and competition, the support of the local government unit and the school, and the awards and recognition they received are examined in the context of the conservation of this musical tradition now threatened by modern music and tenologically complex instruments. Theoretically, the rondalla as performance medium or craft has become a source of individual or community pride and is considered as an important factor in the present enthusiasm to perpetuate this tradition in Dauin's cultural life and identity. We conclude that bu having both the school-based and community-based rondalla as complementary venues for expressing musical talent,. the appreciation of this tradition is broadened in a manner that is sustainable across time and space.